Restoring tracheal defects in a rabbit model with tissue engineered patches based on TGF-β3-encapsulating electrospun poly(l-lactic acid-co-ε-caprolactone)/collagen scaffolds. (31st October 2018) - Jing, Hui; Gao, Botao; Gao, Manchen; Yin, Haiyue; Mo, Xiumei; Zhang, Xiaoyang; Luo, Kai; Feng, Bei; Fu, Wei; Wang, Jing; Zhang, Wei; Yin, Meng; et al.
Abstract: Long segment tracheal stenosis often has a poor prognosis due to the limited availability of materials for tracheal reconstruction. Tissue engineered tracheal patches based on electrospun scaffolds and stem cells present ideal solutions to this medical challenge. However, the established engineering process is inefficient and time-consuming. In our research, to optimize the engineering process, core–shell nanofilms encapsulating TGF-β3 were fabricated as scaffolds for tracheal patches. The morphological and mechanical characteristics, degradation and biocompatibility of poly(l -lactic acid-co-ε-caprolactone)/collagen (PLCL/collagen) scaffolds with different compositions (PLCL:collagen 75:25, 50:50 and 25:75, respectively) were comparatively evaluated to determine the preferable compositional ratio. Then the chondrogenesis-inducing potential is investigated, and tracheal patches based on electrospun scaffolds and bone marrow mesenchymal stem cells (BMSCs) were constructed to restore tracheal defects in rabbit models. The results indicated that core–shell scaffolds with a PLCL/collagen proportion of 75:25 were eligible for tracheal patches. The stable and sustained release of TGF-β3 from scaffolds could efficiently promote the chondrogenic differentiation of BMSCs and shorten the incubation time. Tracheal integrity was well maintained for 2 months after restoration; meanwhile, re-epithelialization also achieved. In conclusion, TGF-β3-encapsulating core–shell electrospun scaffolds with a PLCL/collagen proportion of 75:25 could be used to optimize engineering process of tracheal patches.